2021
DOI: 10.1017/s0031182021001670
|View full text |Cite
|
Sign up to set email alerts
|

Use of helminth therapy for management of ulcerative colitis and Crohn's disease: a systematic review

Abstract: The incidence rate of inflammatory bowel diseases is increasing in developed countries. As such there is an increasing demand for new therapies. The aim of this systematic review was to investigate whether there is evidence to support the use of helminth therapy for the management of Crohn's disease and ulcerative colitis. Four databases (PubMed, Embase, Medline and the Cochrane Central Register of Control Trials) were searched for primary evidence in the form of clinical studies. Nine studies were suitable fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…49 Helminthic therapy has been investigated as a treatment for relapsing remitting multiple sclerosis, Crohn's diseases, allergies and asthma. 50 The mechanism of how the helminths modulate the immune response, is unknown. Helminth's relationship to humans as hosts should be classified as mutualistic or symbiotic.…”
Section: Recent Approach In Immunotherapy 921 Allergen Immunotherapymentioning
confidence: 99%
“…49 Helminthic therapy has been investigated as a treatment for relapsing remitting multiple sclerosis, Crohn's diseases, allergies and asthma. 50 The mechanism of how the helminths modulate the immune response, is unknown. Helminth's relationship to humans as hosts should be classified as mutualistic or symbiotic.…”
Section: Recent Approach In Immunotherapy 921 Allergen Immunotherapymentioning
confidence: 99%
“…Most of the studies on the efficacy of helminth therapy in IBD are restricted to animal models. In a recent meta-analysis, Shields and Cooper 106 concluded that it is difficult to reach any conclusion regarding the efficacy of helminth therapy. Nevertheless, helminth therapy is safe and tolerable.…”
Section: Helminths In Ibd Therapeuticsmentioning
confidence: 99%
“…Consequently, parasites and their products are being tested as treatments for autoimmune diseases [ 5 ]. Clinical studies on patients with inflammatory bowel diseases such as ulcerative colitis and Crohn’s disease have shown that nematode infection can reduce inflammation of the intestine and colon [ 6 , 7 ]. Similarly, in patients suffering from multiple sclerosis, a positive outcome of helminth therapy has been observed [ 8 ].…”
Section: Introductionmentioning
confidence: 99%